Breast lesion detection and characterization with contrast‐enhanced magnetic resonance imaging: Prospective randomized intraindividual comparison of gadoterate meglumine (0.15 mmol/kg) and gadobenate dimeglumine (0.075 mmol/kg) at 3T. Issue 4 (15th December 2018) - Clauser, Paola; Helbich, Thomas H.; Kapetas, Panagiotis; Pinker, Katja; Bernathova, Maria; Woitek, Ramona; Kaneider, Andreas; Baltzer, Pascal A.T.
Abstract : Background: Contrast‐enhanced magnetic resonance imaging (CE‐MRI) of the breast is highly sensitive for breast cancer detection. Multichannel coils and 3T scanners can increase signal, spatial, and temporal resolution. In addition, the T1 ‐reduction effect of a gadolinium‐based contrast agent (GBCA) is higher at 3T. Thus, it might be possible to reduce the dose of GBCA at 3T without losing diagnostic information. Purpose: To compare a three‐quarter (0.075 mmol/kg) dose of the high‐relaxivity GBCA gadobenate dimeglumine, with a 1.5‐fold higher than on‐label dose (0.15 mmol/kg) of gadoterate meglumine for breast lesion detection and characterization at 3T CE‐MRI. Study Type: Prospective, randomized, intraindividual comparative study. Population: Eligible were patients with imaging abnormalities (BI‐RADS 0, 4, 5) on conventional imaging. Each patient underwent two examinations, 24–72 hours apart, one with 0.075 mmol/kg gadobenate and the other with 0.15 mmol/kg gadoterate administered in a randomized order. In all, 109 patients were prospectively recruited. Field Strength/Sequence: 3T MRI with a standard breast protocol (dynamic‐CE, T2 w‐TSE, STIR‐T2 w, DWI). Assessment: Histopathology was the standard of reference. Three blinded, off‐site breast radiologists evaluated the examinations using the BI‐RADS lexicon. Statistical Tests: Lesion detection, sensitivity, specificity, and diagnostic accuracy were calculated per‐lesion and per‐region, and compared by univariate and multivariate analysis (Generalized Estimating Equations, GEE). Results: Five patients were excluded, leaving 104 women with 142 histologically verified breast lesions (109 malignant, 33 benign) available for evaluation. Lesion detection with gadobenate (84.5‐88.7%) was not inferior to gadoterate (84.5–90.8%) ( P ≥ 0.165). At per‐region analysis, gadobenate demonstrated higher specificity (96.4–98.7% vs. 92.6–97.3%, P ≤ 0.007) and accuracy (96.3–97.8% vs. 93.6–96.1%, P ≤ 0.001) compared with gadoterate. Multivariate analysis demonstrated superior, reader‐independent diagnostic accuracy with gadobenate (odds ratio = 1.7, P < 0.001 using GEE). Data Conclusion: A 0.075 mmol/kg dose of the high‐relaxivity contrast agent gadobenate was not inferior to a 0.15 mmol/kg dose of gadoterate for breast lesion detection. Gadobenate allowed increased specificity and accuracy. Level of Evidence : 1 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;49:1157–1165.